From skin lesions to multi-organ involvement: organ tropism and pathogenesis of mpox virus - Rupp, Anna-Lena; Meister, Jo; Schulze Zur Wiesch, Julian; Meister, Toni Luise (iScience, 2025)
Mpox virus (MPXV), the causative agent of mpox, is a re-emerging zoonotic orthopoxvirus. Until 2022, infections were largely confined to endemic regions in Central and West Africa. However, following phylogenetic divergence and a subsequent global outbreak in 2022 caused by clade IIb, distinct from the clade I-driven resurgence in the Democratic Republic of the Congo in 2024, MPXV has emerged as a significant global health concern. While mpox is primarily characterized by its distinctive skin lesions, growing clinical and experimental evidence suggests that MPXV can replicate and disseminate to further organ systems, potentially contributing to disease severity. Despite this growing knowledge, the mechanisms underlying MPXV organ tropism and pathogenesis remain poorly understood, posing ongoing challenges for research and clinical management. This review summarizes the latest clinical, pathological, and experimental findings to provide an updated understanding of MPXV tropism and pathogenesis.